Functional Dyspepsia in Review: Pathophysiology and Challenges in the Diagnosis and Management due to Coexisting Gastroesophageal Reflux Disease and Irritable Bowel Syndrome - Shadi S. Yarandi; Jennifer Christie (Gastroenterology Research and Practice)
Functional dyspepsia is a common disorder which imposes significant diagnostic and treatment challenges for patients and physicians. The most recent update of the diagnostic criteria subdivides functional dyspepsia into two subcategories based on the main symptom of epigastric pain or postmeal fullness. As we discuss in this review, several studies have shown significant overlap in symptoms and pathophysiology between functional dyspepsia, irritable bowel syndrome, and the spectrum of reflux disorders. This overlap in symptoms can be informative in helping us to understand the underlying pathophysiology, diagnostic approaches, and treatment strategies. The addition of diagnostic testing such as pH impedance manometry of the distal esophagus to the current common diagnostic tests might be helpful in distinguishing between functional dyspepsia and reflux disease. Importantly, various treatment modalities may be more effective than others if the main symptom is burning rather than pain or postmeal fullness rather than early satiation.